1997
DOI: 10.1542/peds.100.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With HIV Testing Among Sexually Active Adolescents: A Massachusetts Survey

Abstract: Among sexually active Massachusetts adolescents, voluntary HIV testing is uncommon. Teens who have had multiple sexual partners and who do not believe condoms are effective in preventing transmission were most likely to have been tested. Issues requiring clearer communication to patients include the testing process, its availability, and confidentiality. Physicians can play an influential role in the promotion of HIV testing by discussing HIV risk behaviors with patients and offering those at risk voluntary HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 25 publications
3
62
0
3
Order By: Relevance
“…Other investigators have found that adolescents, even those who engage in behaviors that put them at risk for HIV infection, rarely seek HIV testing. A survey of 567 sexually active Massachusetts adolescents, by Samet et al, 21 found that only 22% had had HIV testing and that fewer than one half of the tested adolescents initiated the request for testing. The majority of adolescents in that survey were tested as a result of routine medical screenings, similar to the reasons cited in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have found that adolescents, even those who engage in behaviors that put them at risk for HIV infection, rarely seek HIV testing. A survey of 567 sexually active Massachusetts adolescents, by Samet et al, 21 found that only 22% had had HIV testing and that fewer than one half of the tested adolescents initiated the request for testing. The majority of adolescents in that survey were tested as a result of routine medical screenings, similar to the reasons cited in this study.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Similar trends have been observed among female adolescents. Smith et al 26 found that among the predominantly (93%) female adolescent and young adult (aged [13][14][15][16][17][18][19][20][21][22] population that attends family planning clinics, at least 78% reported engaging in HIV-related risk behaviors such as having sex without a latex condom, but only 45% requested HIV testing. Conversely, in a study of homeless and low-income women who were aged 18 to 55 in Los Angeles, 83% of women reported having been tested for HIV.…”
Section: Resultsmentioning
confidence: 99%
“…The most common reasons youth, including Aboriginal youth, seek an HIV test are because they have been advised by a health care worker; have engaged in a high risk behavior (i.e., injection drug use, unprotected sex); for prenatal screening; or because they are feeling sick (Bucharski et al, 2006;Grant et al, 2006;Mackellar et al, 2006;RotheramBorus, Gillis, Reid, Fernandez, & Gwadz, 1997;Samet & Winter, 1997). Very little information is available about youth perceptions on test counseling; however, one study of HIV testing sites in the USA reported that only 28% of youth said the counselor did a ''good'' job helping them identify their HIV risk behaviors (Schneir, Belzer, & Adivi, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries like United States of America, acceptance rates varied widely (3-100%) depending on the settings. It was in general higher among STDs patients and individuals at high risk for acquiring or transmitting HIV infection than among other populations like women attending family planning clinics [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%